Association of clinical features and myositis-specific antibodies in idiopathic inflammatory myopathy: a retrospective study from southern China - Li, Can; Zheng, Yushi; Zhang, Yu; Ye, Yujin; Zhang, Hui; Yang, Niansheng; Wang, Shuang (Frontiers in Immunology, 2025)
This study aimed to investigate the profiles of myositis-specific autoantibodies (MSA) and their correlation with distinct clinical features in patients with idiopathic inflammatory myopathy (IIM) in southern China. We retrospectively analyzed the medical records of 208 IIM patients, collecting data on their demographic variables, clinical manifestations, comorbidities, and MSA test results. Of the 208 patients, 185 were positive for MSAs. 69 patients were anti-MDA5 positive, 61 patients were anti-ARS positive followed by anti-SRP (34), anti-TIF1-γ (26), anti-Mi-2β (10), anti-NXP2 (10), anti-HMGCR (9), anti-Mi-2α (6), anti-cN-1A (6), and anti-SAE1 (1). Distinct clinical phenotypes were strongly associated with specific antibodies. Anti-MDA5 positive patients had shorter disease duration, less muscle involvement, but higher rates of rash, alopecia, arthritis, fever, and ILD with poorer prognosis. Anti-ARS positive patients had longer disease duration, mechanic’s hands, arthritis, fever, and ILD, but better prognosis. Both anti-MDA5 and anti-ARS antibodies were independent risk factors for developing ILD. Anti-TIF1-γ and anti-Mi-2 were most detected in IIM patients combined with malignancies, and nasopharyngeal carcinoma was the most common malignant tumor. Furthermore, hyperlipidemia and elevated cardiac biomarkers were frequently observed, particularly in patients positive for anti-SRP. The 3-month survival rate for anti-MDA5 positive patients was 87.8%, with all deaths attributed to rapidly progressive-ILD (RP-ILD). In contrast, other antibody positive patients had a 100% survival rate. This comprehensive analysis of a southern Chinese IIM cohort underscores that MSA profiles can effectively stratify patients into clinically distinct subgroups, which is crucial for predicting specific organ involvement, prognosis, and developing tailored treatment strategies.